Behavioral and Emotional Problems in Young People with Pervasive Developmental Disorders: Relative Prevalence, Effects of Subject Characteristics, and Empirical Classification - Lecavalier, Luc (Journal of autism and developmental disorders, 2006)
Parents or teachers rated 487 non-clinically referred young people with Pervasive Developmental Disorders on the Nisonger Child Behavior Rating Form. The objectives of the study were to examine the relative prevalence of specific behavior problems, assess the impact of subject characteristics, and derive an empirical classification of behavioral and emotional problems for this population. Results indicated that the youngsters experienced high rates of behavior and emotional problems. Cluster analysis suggested that six- and eight-cluster solutions best fit the ratings provided by parents and teachers, respectively. Both parent and teacher cluster solutions contained groups of children characterized as problem free, well adapted, hyperactive, anxious, and with undifferentiated behavior disturbances. The empirically derived clusters were supported by data external to the analyses.